1994
DOI: 10.1007/bf02229873
|View full text |Cite
|
Sign up to set email alerts
|

Basement membrane proteins in synovial membrane: Distribution in rheumatoid arthritis and synthesis by fibroblast-like cells

Abstract: Rheumatoid arthritis is a complex disease of unknown origin. In consequence of some immunological reactions, proliferative invading synovial tissue leads to destruction of normal joint architecture. The aim of this study was to investigate qualitative changes in extracellular matrix distribution of proliferating rheumatoid synovium and their cellular origin. Synovial tissues from 57 clinically indicated arthrotomies were investigated with immunofluorescence, using specific antibodies against extracellular matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…This finding is in agreement with immunofluorescence studies showing a collagen type-IV staining in cultured FLS [28]. In vitro, no differences in the baseline gene expression for collagen type IV were observed between RA-FLS and OA-FLS.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This finding is in agreement with immunofluorescence studies showing a collagen type-IV staining in cultured FLS [28]. In vitro, no differences in the baseline gene expression for collagen type IV were observed between RA-FLS and OA-FLS.…”
Section: Discussionsupporting
confidence: 94%
“…In chronic synovitis, cytokines may induce a degradative phenotype in SLCs [15]. In situ and in vitro studies have shown that fibroblast-like synovial cells (FLSs) synthesize collagen type IV [19,28]. Since collagen type IV is regarded as a major structural component of the basement membrane, we investigated the in situ distribution of this structural protein using immunochemistry in synovia with chronic synovitis from patients with osteoarthritis (OA) and rheumatoid arthritis (RA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the synovial membrane has a basement membrane-like structure in synovial lining layer and the synovial lining layer shows an epitheliallike arrangement (23,(40)(41)(42)(43)(44). Several immunohistochemical studies have demonstrated that the synovial lining cells produce the constituents of basement membranes, such as laminin and type IV collagen (40)(41)(42)(43)(44). In the rat TMJ, Nozawa-Inoue et al (44) demonstrated that a discontinuous basement membrane-like structure was present around the synovial type B cells, but not type A cells nor fibroblasts of a sublining layer under electron microscopic investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Not only the number of laminin receptors but also the production of laminin itself is upregulated in the synovial lining. Besides endothelial cells, SFs produce and secrete laminin, and its deposition at the synovial lining is increased in RA [28]. Along with collagen and fibronectin, laminin promotes adhesion and proliferation of synovial cells and lymphocytes.…”
Section: Laminin-binding Integrins α3β1 and α6β1mentioning
confidence: 99%